Activation of PTK receptors in solid human tumors - Pierotti, Marco (Henry Stewart Talks, 2007)
The human kinome, Role of tyrosine kinases in cancer, Mechanisms of activation of RTKs in physiological and pathological conditions, Autocrine Loop, The dermatofibrosarcoma protuberans model, Gene Amplification, the breast cancer model, Mutation, The EGFR and lung cancer model, The Ret and multiple endocrine type 2 syndrom model, Gene rearrangment, The RET and TRK in papillary thyroid carcinoma model, Thyrosine Kinases and therapeutic targets, The Gleevec paradigm, The EGFR inhibitors a new paradigm
Archived at 2018/05/31